Main Landmarks in Fostering Written English Language Skills - Žindžiuvienė, Irena (Acta Paedagogica Vilnensia, 2003)
The increasing use of English has in recent years helped transform the aims and methodology of teaching English in Lithuanian institutions. The role of the English language in the world has encouraged many teachers of English to search for new ways of teaching this popular language. However, very often the teaching and learning process becomes a set of fragmented activities, the main principle of modern textbooks. Teachers who use these teaching means are free from obligation to relate the aspects of a foreign language to the native ones and fail to take into account the questions of language interference and transposition. Besides, such teaching means do not encourage logical development of ideas; this has been proved by the research that has been carried out in order to evaluate students’ writing competence and the influence of fragmentary activities. Taking into consideration the fact that Lithuania is on the road of globalization, one of the problems that has become most urgent lately is ability to communicate with the world, with the emphasis on written communication. The idea of the research has been initiated by comparatively poor organization of teaching and learning writing in English. Students’ writing competence has decreased significantly and has become inadequate to the present global needs. Consequently, English language teachers face a task to fill up this gap and pay more attention to the improvement of students’ writing skills through the activities of all the stages of teaching and learning English writing. The article analyses the research which consisted of the evaluation of students’ writing skills without a preparatory stage and after the preparatory stage. The research was based on the analytical scoring method. Research results prove the fact that fragmentary tasks should be avoided as much as possible in the process of teaching and learning English writing. Teaching writing as logical and coherent development of ideas in written is mistakenly ignored and has to be emphasized at the secondary level, aiming at the correct and logical exposition of the ideas in written English.